(untitled) (International Journal of Innovative Computing, 2021)
Requirements negotiation involves discussion on the requirements conflict to have some compromise that will satisfy the participating stakeholders of a software project. The output of a requirement negotiation is a set of satisfied requirements of two or more parties. In this paper, we present a systematic review of requirements negotiation challenges. The study adopted 34 papers from the final study selection process which were analyzed based on the requirements negotiation challenges they addressed. The identified challenges are decision-making, communication, performance, managing requirement changes, and conflict resolution. The output of the study indicates that decision-making is addressed by 33% of the studies reviewed, followed by the performance with 22%, conflict resolution with 19%, while 16% focus on stakeholders’ communication, and managing requirements changes has 10%.